ANALYSIS OF EXCHANGE RATE PASS-THROUGH, FEAR OF FLOATING, AND IMPLEMENTATION OF INFLATION TARGETING FRAMEWORK - Agung Satryo; Lukytawati Anggraeni (IPB University, 2016)
This paper analyze the exchange rate pass-through and fear of floating behavior on 18 countries that adopting Inflation Targeting Framework (ITF). Vector Error Correction Model (VECM) is used: (1) to estimate the effect of exchange rate depreciation to inflation (passthrough); and (2) to examine the indication of fear of floating behavior. The result shows that passthrough effect has decreased in most countries after ITF where middle income countries have higher passthrough than high income countries. This effect did not disappear completely and still has a significant role to drive inflation. The interventions on exchange rate movement can be interpreted more as control of inflation than fear of floating. The implementation of ITF especially in middle income countries needs further to be reconsidered since it requires inflation as the only nominal anchor.